Passive isolator design and vibration damping of EO/IR gimbal used in UAVs - YAYLA, PAŞA (My University, 2023)
One of the most critical factors affecting the quality of the images captured by the surveillance systems used in the unmanned aerial vehicles is the vibrations transmitted from the aircraft to the gimbal. The gimbal used in unmanned aerial vehicles is essential equipment, holding the camera steadily and accurately and pointing it in the desired direction. Within the scope of this article, a passive vibration isolation system design has been made for the two-axis electro-optical gimbal used in the mini unmanned aerial vehicle. By choosing the spring-damper system among different methods, the design that isolates the harmonic vibration from the platform on a single axis has been made using the analytical method. The analytical method was used to create a design that isolates the harmonic vibration from the platform along a single axis. In addition, the part named 'Pan Yoke', which contains this damper system, was designed with a computer-aided design program, and natural frequency values were checked with Ansys modal analysis. The frequency of the vibration transmitted from the air vehicle to the gimbal and the natural frequency of the designed part have been determined to be close to each other, at around 200 Hz. The natural frequency values of this part were optimised with various design changes and topology optimisations to prevent the part from resonating.
Keywords: assive vibration isolators; Harmonic vibration; Unmanned aerial vehicles; Ansys modal analysis; Topology optimisation